2020
DOI: 10.21203/rs.2.20379/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin run-on sequencing analysis finds that ECM remodeling plays an important role in canine hemangiosarcoma pathogenesis

Abstract: Background Canine visceral hemangiosarcoma (HSA) is a highly aggressive cancer of endothelial origin that closely resembles visceral angiosarcoma in humans, both clinically and histopathologically. Currently there is an unmet need for new diagnostics and therapies for both forms of this disease. The goal of this study was to utilize ChRO-seq and immunohistochemistry (IHC) to identify gene and protein expression signatures that may be important drivers of HSA progression. Methods Chromatin run-on sequencing (Ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Our study showed that LAMA4 was highly expressed in HCC tumor tissues. Considering that LAMA4 is closely related to the migration of cancer cells and tumor progression in a series of tumors, the the latest research describes LAMA4 as "oncolaminin" [17]. The crosstalk between Notch and TGF-β1 has been reported many times.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that LAMA4 was highly expressed in HCC tumor tissues. Considering that LAMA4 is closely related to the migration of cancer cells and tumor progression in a series of tumors, the the latest research describes LAMA4 as "oncolaminin" [17]. The crosstalk between Notch and TGF-β1 has been reported many times.…”
Section: Discussionmentioning
confidence: 99%